The economic analysis of labour - Fisher, Malcolm R. (London : Weidenfeld and Nicolson, 1971)
The study reiterates the importance of occupational history in the activity selection processes of an individual threading his way through a working lifetime.
Includes index.
Includes bibliographical references: p. 279-290.
rpm 19/02/2018
Loans
Keywords: Labor economics